Global trends, inequalities, and pathogen shifts in infectious diarrhea among children under five: a comprehensive analysis of the global burden of disease study 1990–2021 - Tian, Qiangqiang; Zheng, Ya; Li, Yishudong; Wu, Rui; Lin, Yuyu; Chen, Zhaofeng (Frontiers in Nutrition, 2025)
BackgroundInfectious diarrhea is a major cause of morbidity and mortality among children under five, particularly in low- and middle-income countries. Despite notable improvements in public health, substantial regional, national, and socioeconomic disparities persist, while the evolving pathogen spectrum presents new challenges for prevention and control.MethodsWe conducted a comprehensive analysis using data from the Global Burden of Disease (GBD) 2021 cycles, covering 204 countries and territories from 1990 to 2021. We assessed incidence, prevalence, mortality, and disability-adjusted life years (DALYs) at global, regional, national, and SDI quintile levels. Analytical methods included calculation of age-standardized rates (ASR), estimation of annual percentage changes (EAPC), joinpoint regression, inequality indices (SII and concentration index), frontier analysis, and pathogen-specific DALY trends.ResultsGlobally, incident cases and DALYs increased while ASRs for all burden indicators declined substantially from 1990 to 2021. The heaviest burdens persisted in South Asia and Western Sub-Saharan Africa. Although absolute global inequalities lessened, relative disparities in mortality and DALYs widened. Temporal and geographic heterogeneity was evident, with high-income countries increasingly affected by viral etiologies. Frontier analysis revealed notable inefficiency gaps for several countries. Major pathogen-related DALY reductions were observed for rotavirus and Shigella, yet viral causes gained relative prominence in high-SDI settings.ConclusionWhile marked global progress has been achieved in reducing childhood infectious diarrhea burden, persistent, and sometimes widening inequities remain. Enhanced investment in equitable health systems, renewed pathogen surveillance, and adaptive, targeted interventions are needed to sustain and accelerate progress, particularly in the most affected regions.